All Days 2005
DOI: 10.2118/94511-ms
|View full text |Cite
|
Sign up to set email alerts
|

Production Enhancement From Sand Management Philosophy: A Case Study From Statfjord and Gullfaks

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractStatfjord and Gullfaks are "Brown" fields operated by Statoil in the Tampen area of the North Sea. The production from these fields is characterized by large volumes of water and increasing sanding tendencies. The operator has for many years followed a strategy whereby sand produced with the wellstreams has been handled topsides prior to on-site disposal. The adoption of a sand management strategy has been crucial for prolonging economic reservoir development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Even with exclusionary well design, solids will report to the surface facilities through equipment failure, completion limitations, or a step change in production profile, such as water breakthrough. In addition, an operating model of sand coproduction is becoming more relevant as a method of improved oil recovery (Geilikman et al 1994;Ahmad et al 2004;Andrews et al 2005). Facilities sand management is tasked with ensuring sustained hydrocarbon production when particulate solids are present in well fluids, while minimizing the impact of these produced solids on surface equipment (Rawlins 2013).…”
Section: Produced Solids In Separatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with exclusionary well design, solids will report to the surface facilities through equipment failure, completion limitations, or a step change in production profile, such as water breakthrough. In addition, an operating model of sand coproduction is becoming more relevant as a method of improved oil recovery (Geilikman et al 1994;Ahmad et al 2004;Andrews et al 2005). Facilities sand management is tasked with ensuring sustained hydrocarbon production when particulate solids are present in well fluids, while minimizing the impact of these produced solids on surface equipment (Rawlins 2013).…”
Section: Produced Solids In Separatorsmentioning
confidence: 99%
“…The preferred location for facilities sand removal is before the choke with a wellhead desander (Rawlins 2013); however, in cases where this technology is not currently used, the produced solids will collect in the primary separating vessel. Accumulated solids in gravity-settling vessels result in loss of residence time, corrosion-enhancement zones, increased sediment in oil, increased oil content in produced water, and degraded injectivity of produced water (Andrews et al 2005). Sand and solids…”
Section: Produced Solids In Separatorsmentioning
confidence: 99%
“…Sand production has been experienced throughout the production history, requiring a passive sand management strategy (Andrews et al 2005). The field produces from two main reservoirs, with reservoir temperatures from 90 o C to 95 o C. From initial field development to 2005, wells were mainly completed with a cemented and perforated liner.…”
Section: Field Historymentioning
confidence: 99%
“…The application proposed in this paper concerns deterioration of choke valves undergoing erosion (Bringedal et al, 2010;Andrews, Kjørholt & Jøranson, 2005). In offshore oil platforms, choke valves are used on the surface to control the flow of hydrocarbons and protect the equipment from unusual pressure fluctuations.…”
Section: Deterioration Of Choke Valvesmentioning
confidence: 99%
“…In offshore oil platforms, choke valves are used on the surface to control the flow of hydrocarbons and protect the equipment from unusual pressure fluctuations. Production experience has shown that choke valves are prone to sand erosion in the disks and in the outlet sleeve (Andrews et al, 2005). The main parameters determining erosion are the impact velocity and the impact angle of the sand grains through the choke discs.…”
Section: Deterioration Of Choke Valvesmentioning
confidence: 99%